2007
DOI: 10.1111/j.1524-475x.2007.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent ischemia impairs myofibroblast development in wound granulation tissue: A new model of delayed wound healing

Abstract: We describe a new animal model designed to assess the impact of ischemia on wound healing. Eight patterns of arterial lesion in the limb were first tested in 24 Wistar rats. Resection of the external iliac artery down to the femoral artery at the level of the knee was chosen as the reference model and performed on the left limb of 45 rats; the right limb was used as the control. Skin wounds measuring 1.2 x 0.8 cm were created on both feet. Ischemia was assessed by blood flow measurement, which decreases dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…These data support the notion of acute low O 2 as a positive stimulator of wound healing (Frangogiannis et al, 2000). The upregulation of TGFb1 in hypoxic dermal rat wounds (Alizadeh et al, 2007) is consistent with our results showing increased levels of active and total TGFb1 in response to the low-O 2 switch. The absence of effects of TGFb1 in these conditions may be partly due to the concomitant downregulation of the TGFb-RII shown here, possibly by a negative TGFb1 feedback loop.…”
Section: Hypoxia Inhibits Skin Myofibroblast Differentiationsupporting
confidence: 91%
See 2 more Smart Citations
“…These data support the notion of acute low O 2 as a positive stimulator of wound healing (Frangogiannis et al, 2000). The upregulation of TGFb1 in hypoxic dermal rat wounds (Alizadeh et al, 2007) is consistent with our results showing increased levels of active and total TGFb1 in response to the low-O 2 switch. The absence of effects of TGFb1 in these conditions may be partly due to the concomitant downregulation of the TGFb-RII shown here, possibly by a negative TGFb1 feedback loop.…”
Section: Hypoxia Inhibits Skin Myofibroblast Differentiationsupporting
confidence: 91%
“…Our previous work using a rat hind-limb ischemic wound model suggested that reduced wound contraction in ischemic conditions is related to decreased myofibroblast differentiation (Alizadeh et al, 2007). Conversely, hypoxic culture has been shown to stimulate fibrosis and myofibroblast activity in vessels (Das et al, 2002;Krick et al, 2005;Zhang et al, 2005), lung (Short et al, 2004;Leufgen et al, 2005;Jiang et al, 2006), liver, and kidney (Manotham et al, 2004;Shi et al, 2007).…”
Section: Hypoxia Inhibits Skin Myofibroblast Differentiationmentioning
confidence: 96%
See 1 more Smart Citation
“…An increased oxygen demand is necessary for normal tissue repair, which is not sufficiently covered under hypoxic conditions, and wound healing may be attenuated due to the suppression of essential oxygen-dependent processes such as fibroblast and myofibroblast activity, angiogenesis, and collagen synthesis (2,9). An ameliorated oxygen supply was most likely responsible for the improved midline suture healing in the HbV-treated animals in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Using an ischemic limb model, persistent hypoxia was shown to reduce production of collagenous matrix and retard granulation tissue formation as well as reduce contraction in a cutaneous wound. 40 On the other hand, defective granulation tissue formation and delayed dermal regeneration in diabetic mice wounds were improved by increasing the stabilization of HIF-1. 1 Additionally, HIF-1a gene transcription was found to be impaired in dermal fibroblasts of aged mice resulting in delayed angiogenic responses in ischemic wounds.…”
Section: Hif-1 Deficiencymentioning
confidence: 99%